A escrita (des)obediente das "memórias apóstumas" de Uanhenga Xitu - Conceição, Simone Ribeiro da (2010)
The present dissertation aims to analyze the narrative in O Ministro (1989), a novel by Uanhenga Xitu, with especial attention to the way the text reflects his obedience and disobedience to the cultural matrixes which form the Angolan nation. Preliminaries considerations about the life and work of Uanhenga Xitu have indicated that there was in it a configuration of an un-colonial option which have motivated the historical subject to participate in the political movement for the independence of Angola. In addition, this movement has determined the creation of a literary project marked by an ideological commitment to the Angolan national project. In this present study we aim to demonstrate that such ideological commitment is present in Xitu s testimonial writing and fictional work used to create a heterogeneous narrative defined by the author as his un-posthumous memories. Through a cartographical perspective, our analysis intends to emphasize the evidences of the prevailing proceedings used by the author not only to transform the testimonial voice into a disobedience to the constructed knowledge on the recent Angolan political history but also to use it to recover the narrative forms and themes that denotes a pact with the oral tradition. Based on the Cultural Studies, we aim to show that Uanhenga Xitu s narrative makes room for other memories, breaking up the autobiographical pact implied by the title. Therefore, his (dis)obedient writing becomes a strategy that allows him to disseminate the Angolan cultural legacy inside and outside his own location of culture